Creation of Added Value of Traditional Weaving Products of the Thai Puan People in Pak Phli District, Nakhon Nayok Province to Commercialization - Wewa, Suthawadee; Khucharoenphaisan, Khwanchai (Arts of Management Journal, 2023)
This study examines the creation of value-added products of traditional weaving fabrics of the Thai Puan people in Pak Phli District, Nakhon Nayok Province for commercial purposes specifically. The objectives were 1) to increase the value of the prototype product processing, 2) to transfer technology to the Thai Puan weaving group, 3) to disseminate the prototype product processing manual and 4) to create an economy for the community to move towards commercialization. The results showed that most of the respondents were female (98 percent), aged between 41-50 years old (48 percent), and most of the sample's education level was higher than a master's degree (48 percent).) Most of them are self-employed/independent businesses (76 percent) and the monthly income of most of the samples earns more than 20,000 baht (50 percent) in the satisfaction assessment form of woven fabric products of the Thai Phuan people in the overall average all 4 aspects. The type with the highest satisfaction score was type 4 (4.44 - most) and the lowest type was type 3 (4.02 - more). The suggestion for further research is to study the development of products that have multiple uses in one piece, such as a bag and it can also be a doll or display item in the same piece by folding or turning the fabric, etc., to create novelty for the community's products. The study also suggests increasing distribution channels to increase a variety of consumer groups at all levels of society and the study of the application of new fabric patterns from traditional patterns including giving the color according to the fashion of that era for a variety of raw materials that will be processed into new products.